The effect of heterobifunctional crosslinkers on HEMA hydrogel modulus and toughness - Boazak, Elizabeth M. (PLoS One, 2019)
The use of hydrogels in load bearing applications is often limited by insufficient toughness. 2-Hydroxyethyl methacrylate (HEMA) based hydrogels are appealing for translational work, as they are affordable and the use of HEMA is FDA approved. Furthermore, HEMA is photopolymerizable, providing spatiotemporal control over mechanical properties. We evaluated the ability of vinyl methacrylate (VM), allyl methacrylate (AM), and 3-(Acryloyloxy)-2-hydroxypropyl methacrylate (AHPM) to tune hydrogel toughness and Young’s modulus. The crosslinkers were selected due to their heterobifunctionality (vinyl and methacrylate) and similar size and structure to EGDMA, which was shown previously to increase toughness as compared to longer crosslinkers. Vinyl methacrylate incorporation into HEMA hydrogels gave rise to hydrogels with Young’s moduli spanning ranges for ligament to cartilage, with a peak toughness of 519 ± 70 kJ/m(3) under physiological conditions. We report toughness (work of extension) as a function of modulus and equilibrium water content for all formulations. The hydrogels exhibited 80%-100% cell viability, which suggests they could be used in tissue engineering applications.